2016
DOI: 10.1111/head.12948
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8 and Migraine

Abstract: Migraine is among the most common diseases on earth and one of the most disabling, the latter due in large part to poor treatment efficacy. Development of new therapeutics is dependent on the identification of mechanisms contributing to migraine and discovery of targets for new drugs. Numerous genome-wide association studies (GWAS) have implicated the transient receptorpotential M8 (TRPM8) channel in migraine. This channel is predominantly expressed on peripheral sensory neurons and is known as the sensor for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 91 publications
(217 reference statements)
0
65
0
Order By: Relevance
“…Using FG to label dural afferent neurons in TRPM8 EGFPf/+ mice, we found that only 3%‐4% of dural afferent neurons express TRPM8 channels in adult mice, much lower than the percentage of total TG neurons expressing TRPM8 (10%). This is surprising, given that activation of dural TRPM8 channels significantly modifies headache‐related behaviors in rodent models . It is possible that we may underestimate the abundance of dural afferent neurons expressing TRPM8, as we removed the muscle and periosteal sheath on the skull before tracer application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using FG to label dural afferent neurons in TRPM8 EGFPf/+ mice, we found that only 3%‐4% of dural afferent neurons express TRPM8 channels in adult mice, much lower than the percentage of total TG neurons expressing TRPM8 (10%). This is surprising, given that activation of dural TRPM8 channels significantly modifies headache‐related behaviors in rodent models . It is possible that we may underestimate the abundance of dural afferent neurons expressing TRPM8, as we removed the muscle and periosteal sheath on the skull before tracer application.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising, given that activation of dural TRPM8 channels significantly modifies headache-related behaviors in rodent models. [6][7][8] It is possible that we may underestimate the abundance of dural afferent neurons expressing TRPM8, as we removed the muscle and periosteal sheath on the skull before tracer application. This minimizes labeling of the pericranial afferent neurons in TG, but may damage the axon collaterals of dural afferent neurons that innervate pericranial tissues through the calvarial sutures 13,14 and cause neuronal death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acutely, many patients find heat or cold packs, a hot shower, or a combination of these beneficial in dampening down the pain of migraine or tension‐type headache . Some patients find topical treatments such as herbal balms with small amounts of menthol or camphor (one of the main components of Tanacetum parthenium ) applied to the temples, forehead, or base of the neck helpful . Inhalation of lavender essential oil for 15 minutes may be helpful for some patients with migraine .…”
Section: Chronic Migraine Prophylaxismentioning
confidence: 99%